The Influence of Picture Coloring Activities on the Fine Motor Skills of Children Aged 5-6 Years - Durrotunnisa; Noflis Noflis; Zakiyyatul Zakiyyatul; Nurhayati Nurhayati (Universitas Negeri Semarang, 2025)
This study was conducted to address the limited development of fine motor skills among children in Group B2 at Bungamputi Kindergarten, Palu. The objective of this research was to examine the effect of picture-coloring activities on children’s fine motor skills. A quantitative quasi-experimental design with a one-group pretest–posttest approach was employed. Data were collected through structured observations, teacher interviews, and documentation. The intervention consisted of six coloring sessions using structured images, including fish, sunflowers, beetles, seaside scenery, and rice fields. The results indicated a significant improvement in children’s fine motor skills after the intervention. Children demonstrated better pencil grip control, reduced hand stiffness, improved coloring speed, and greater accuracy in coloring within patterns. Statistical analysis revealed that the t-value (t = 10.203) exceeded the t-table value (2.14479) at df = 14 with a significance level of α = 0.000 (< 0.05), indicating a statistically significant effect. Therefore, the alternative hypothesis (Ha) was accepted, confirming that picture-coloring activities positively influence children’s fine motor skills. It is recommended that future studies explore integrating structured and free drawing activities to further support fine motor development in early childhood education.